Budaya Organisasi dan Pencegahan Fraud dalam Pengelolaan Keuangan Desa dengan Moralitas Individu sebagai Mediasi - Sri Rustiyaningsih (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2023)
This study aims to prove the direct and indirect effects of organizational culture on fraud prevention through individual morality as a mediating variable. This study is a quantitative study. The research was conducted on village objects in the Wungu sub-district, Madiun Regency, with village apparatus respondents who were involved in managing village finances. The census technique was used in this study. Primary data was obtained by distributing questionnaires directly to the respondents. Hypothesis testing uses Path Analysis with the help of the SPSS version 24 program and is strengthened by testing using the online Sobel Test. The research results show that organizational culture significantly positively affects fraud prevention in village financial management. Organizational culture has a significant positive effect on individual morality. Individual morality affects the prevention of fraud in village financial management. However, the results of path analysis testing indicate that individual morality is not proven to mediate the influence of organi-zational culture on fraud prevention in village financial management. These results are supported by the Sobel Test online results which show that individual morality does not mediate the relationship between organizational culture and fraud prevention in village financial management.